Program Kaderisasi Pandita Majelis Buddhayana Indonesia Jawa Barat - Hendra Hendra (LPPM STIAB JINARAKKHITA LAMPUNG, 2026)
Cadre development for Buddhist lay leaders plays a crucial role in sustaining the transmission of the Dhamma; however, empirical studies integrating such programs with canonical Buddhist teachings remain limited. This study examines the Cadre development of prospective Upāsaka/Upāsikā Anu Pandita (U.A.P.) in the Indonesian Buddhayana Council (MBI) of West Java from the perspective of the Dutiyaupaṭṭhākasutta and the Maṅgalasutta. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving administrators, organizers, and participants. The findings indicate that participants’ engagement is driven not merely by instrumental motivations but by spiritual aspirations, reflected in viriya (diligent effort), sustained commitment, and active participation in practicing the Dhamma. The program also enhances participants’ ability to deliver Dhamma teachings in a structured and contextually relevant manner, while strengthening their role as upaṭṭhāka (lay attendants) characterized by service, responsibility, and ethical alignment. This study contributes to Buddhist studies by proposing a conceptual understanding of Cadre development as a process of lay spiritual cultivation grounded in canonical teachings, bridging empirical findings and normative doctrines within contemporary Buddhayana practice.